Comprehensive Review of Chronic Disease Management, Innovations in Care, And Economic Impacts - Al-Kanfari, Abdullah Muhammad Ali; Al Mansour, Saif Ali Saleh; Alyami, Saleh Abdullah Saleh; Alyami, Taleb Rakan; Al Qannah, Lafi Mahdi Saleh; Alrabie, Hassan Mohammed Salem; Majrashi, Tahani Mohammad Ali; Al zuri, Saman Mohmad; Al shahrani, Bada Dhafar abdullah; Al Mahdi , Ali Mahdi Ali (Journal of Ecohumanism, 2024)
Noncommunicable diseases can, therefore, be described as a major global public health challenge, as they affect and involve conditions that are usually lifelong. With the aging of the population and increased prevalence of other risk factors, these diseases are becoming more widespread; therefore, effective control of chronic diseases, including diabetes, hypertension, cardiovascular diseases, and respiratory illnesses, has become a major challenge in most healthcare facilities across the globe. This paper aims to review the existing literature about chronic disease management, emerging trends in the practice, and financial implications of the illness burden. It examines how managed technology, patient-centric care, and policy solutions improve patient status and reduce healthcare expenditure. The review also outlines problems in the healthcare systems and discusses ways of improving the approach to chronic disease management.